Conceptual Analysis of Bakhtin’s Carnivalism and the Examination of Resistance Possibility in Parole - Meymant Atariani; Mehdi Najafzadeh (رهیافتهای سیاسی و بین المللی, 2018)
The purpose of this research is the analysis of the carnivalesque in folk culture and the study of the possibility of resistance against predominate-monophonic political power. Predominate paradigm in the thinking area of new age introduces language as a new instrument of world-understanding and takes the language positional and a result of its social context. Voices indicate different interests, profits and ideologies and thus language is known as the area of social-political litigations. According to Bakhtin's opinion, there are two discourses in every society: serious and informal (humour). The first one mostly denotes governorship and power state that is interpreted stern and silent. The second discourse expresses usual life, language and folk literature and popular festivals. Bakhtin interprets carnivals or festivals of humour as the best position of manifestation and formation of resistance and realizing the polyphony and thus democracy. In this research, we had an inquiry to find and analyze the components of carnavality like as polyphony in order to the assessment of the formation of resistance in utterance based on sociological description. According to Bakhtin, there is an obligatory relationship between the emergence of polyphony in autocratic situation and irony in utterance. This research assumes that this relationship is necessary for possibility of resistance in utterance.